TMS in Communication Oriented Cultures - Ana Maria ANDREI (Revista de Management Comparat International, 2025)
The paper presents a study on transactive memory systems (TMS) and individual’s meta-knowledge (ImetaK) in organizational contexts, examining how communication oriented organizational culture improves the development of Imetak and TMS improving the acquisition, creation, distribution and use of knowledge. The research involved a questionaire based survey applied with 103 professionals from knowledge-intensive business services operating in Romania, and tested hypotheses about the positive effects of communication oriented organizational culture on both individual’s meta-knowledge and team-level transactive memory systems. The empirical results show that an organizational culture that cultivates communication positively influences the development of metaknowledge that employees have about their work environment and colleagues, as well the development of the transactive memory system (TMS) at the team level and the organizational level.